Two Novel Polysaccharides From Clitocybe squamulosa: Their Isolation, Structures, and Bioactivities - Guo, Dongdong; Lei, Jiayu; Xu, Lijing; Cheng, Yanfen; Feng, Cuiping; Meng, Junlong; Chang, Mingchang; Geng, Xueran (Frontiers in Nutrition, 2022)
The crude polysaccharides from the fruiting bodies of Clitocybe squamulosa (CSFP) were isolated by hot-water extraction. Two novel polysaccharides, CSFP1-β and CSFP2-α, were further purified by DEAE-52 anion exchange and Sephacryl S-400 gel filtration chromatography, and the purities reached 98.44 and 97.83%, respectively. The structural characteristics and bioactivities of CSFP, CSFP1-β, and CSFP2-α were identified by the combination of chemical and instrumental analysis. Results showed that CSFP was formed by the aggregation of honeycomb spherical materials; CSFP1-β and CSFP2-α were interwoven by reticular and fibrous structures, respectively. Purified components of both CSFP1-β and CSFP2-α showed typical infrared absorption peaks of polysaccharides, and contents of nucleic acid and protein decreased significantly. Simultaneously, CSFP with a molecular weight (Mw) of 1.948 × 104 Da were composed mainly of glucose, mannose, galactose, and rhamnose. CSFP1-β was composed mainly of glucose, galactose, and mannose, while CSFP2-α was composed of glucose, and both their Mw distributions were uneven. Compared with CSFP, the antioxidant activities of CSFP1-β and CSFP2-α were significantly improved (p < 0.05), and they both showed good abilities to bind free cholesterol and bile acid salts in vitro. The binding abilities of the two compounds were found to be 68.62 and 64.43%, and 46.66 and 45.05 mg/g, respectively. CSFP, CSFP1-β, and CSFP2-α had good bacteriostatic effects with a linear increasing relationship to increasing concentration. In addition, CSFP promoted the growth of RAW264.7 cells and has potential immunomodulatory, anti-inflammatory, and anti-tumor activities.